Development of inhalable microparticles for drug delivery to deep lung tissues - Abbas, Yasmine Houssam ElDin (AUC Knowledge Fountain, 2015)
Lung cancer is the deadliest solid tumor, leading to the deaths of more individuals than the combination of the three next most lethal cancers which are colon, prostate and breast cancer. According to the IARC, in 2012 lung cancer accounted for 13% (1.83 million) of cancer cases and caused 19% (1.56 million) of cancer deaths worldwide. Despite advances in surgery and drug discovery, lung cancer remains difficult to treat. This is a result of unavoidable exposure to carcinogens, poor diagnosis and the lack of targeted drug delivery platforms. The aim of this study was to develop a non-invasive, patient convenient platform for the targeted delivery of chemotherapeutic drugs to cancer in deeper lung tissue. The formulation consisted of inhalable maltodextrin (MD)-based microparticles (MPs) encapsulating chitosan (CS) nanoparticles (NPs) loaded with magnetic nanoparticles (MNPs) and a chemotherapeutic drug. Ionotropic gelation was used for CS NPs synthesis. MNPs were synthesized via hydrothermal method and they were superparamagnetic with magnetic saturation (Ms), coercivity (Hc) and remanence (Mr) of 48.4 Am2/Kg, 9.9x10-4 T and 0.5 Am2/Kg emu/g; respectively. CS NPs provided a sustained release of drug, whereas MNPs encapsulated in CS NPs were able to increase the NP drug release in response to an external magnetic field by 1.7 fold. Cell uptake studies conducted using lung cancer cells (A549) indicated that the CS NPs are rapidly uptaken, and show preferential toxicity to tumor cells in comparison to cultured fibroblasts. NPs were modified with anti-epidermal growth factor receptor antibodies and this modification showed to hinder cellular uptake of NPs. Afterwards, the prepared CS NPs and CS-MNPs were co-spray freeze dried (SFD) with MD. The prepared SFD powders had fine particle fraction (FPF ≤ 5.2 μm) of 40-42 % w/w and mass median aerodynamic diameter (MMAD) of 5-6 μm as determined by the next generation impactor (NGI). A mixture of CS NPs and CS-MNPs could be able to provide a continuous sustained release of drug, with intermittent blouses of drug in response to external stimuli; a drug profile desirable in cancer therapy. In conclusion, the targeted delivery to the lung cancer using the developed formulation seems to be a promising approach.